The art of paper crafts - MacLeod, Jilly (East Granby, CT : Book Express, 1991)
Step-by-step photographs and detailed instructions for designs using paper: from pictures and frames to puppets and mobiles, boxes and bags to gift wraps and greeting cards.
Keywords: Paper work; Handicraft; Greeting cards; Gift wrapping